Influência da glicemia e da sobrecarga de carboidrato na modulação autonômica cardíaca em adultos aparentemente saudáveis - Oliveira, Caroline Maria de (2020)
Glycemic changes and food intake, mainly simple carbohydrates, can cause an increase in the activity of the sympathetic nervous system and, consequently, a reduction in heart rate variability (HRV). The aim of the study was to evaluate the influence of glycemic levels and carbohydrate overload on cardiac autonomic modulation in adults. We evaluated 108 individuals, of both sexes between 18 and 40 years old, non-smokers and without diagnosed diseases divided by the fasting glucose values in a group with lower values (<90.5 mg / dL) and a group with higher values (> 90, 5 mg / dL). HRV (nonlinear indices, without time and frequency domain) was analyzed after fasting, 30 and 60 minutes after ingesting a dextrose overload (0.5 g / kg of body weight). Dextrose overload increased blood glucose after 30 min (142.45 ± 21.08 mg / dl) of intake and although there was a reduction at 60 min (136.11 ± 24.99 mg / dl), values remained higher relation to fasting (91.34 ± 8.34 mg / dl). The values of body mass (69.7 / 52.8-114.7 vs 78.9 / 49.3-123.1 kg), BMI (24.5 / 18.5-45.3 vs 26.6 / 19.6-41.1 kg · m-2) and waist circumference (82.1 / 73-117 vs 90.2 / 66-123 cm) in the group with the highest fasting blood glucose were higher compared to the group with the lowest blood glucose . As expected, the group with the highest glycemia had the highest fasting glycemia (86 / 74- 90 vs 97 / 91-120 mg / dL) and the highest AAC during dextrose overload (7297.5 / 5520.0-8685.0 vs 7897, 5 / 6015.0-10350.0 mg / dLx60min). Obesity indicators were correlated with blood glucose (Rho = 0.295 to 0.485) during fasting and during dextrose overload. Likewise, obesity indicators were negatively correlated with HRV indices both in fasting and during dextrose overload (Rho - 0.192 to - 0.355). Additionally, glycemia both in fasting and during dextrose overload was negatively correlated with several HRV indices, both in the time domain and in the frequency domain (Rho: - 0.192 to - 0.273). In conclusion, individuals with higher values of fasting blood glucose show impaired cardiac autonomic modulation, as well as reduced cardiac autonomic modulation after carbohydrate overload. Additionally, obesity and blood glucose indicators are inversely correlated with cardiac autonomic modulation at rest and carbohydrate overload in adults.